Traffic engineering approaches in P2P environments - Sousa, Pedro (2013)
Nowadays, P2P applications proliferate in the Internet with distinct utilization contexts, being also an attractive model for the deployment of advanced Internet services. However, there are several undesirable effects that are caused by such applications, raising coexistence problems with Internet Service Providers (ISPs). In this context, using as case study BitTorrent like applications, this work explores a collaborative framework allowing that advanced efforts could be carried on between P2P applications and network level entities. In order to illustrate such framework, several Traffic Engineering (TE) mechanisms are devised in order to align some P2P dynamics with particular objectives pursued by network administrators. The simulation results show that both the proposed framework and corresponding illustrative mechanisms are viable and can effectively foster future research efforts within this field.